2018
DOI: 10.31228/osf.io/qbzn5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naskah Akademik Keuangan Desa

Abstract: Undang-undang Nomor 22 Tahun 1999 dan Undang-undang Nomor 25 Tahun 1999 yang telah disempurnakan dengan Undang-undang Nomor 32 Tahun 2004 dan Undang-undang Nomor 33 Tahun 2004 telah mengubah hubungan antara pemerintah pusat dan daerah. Dua uUdang-undang ini digunakan sebagai dasar hukum proses desentralisasi di Indonesia dengan memberikan peranan yang sangat penting kepada pemerintah lokal (kabupaten/kota).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…While men are considered strong, rational, mighty and so on. Stereotype like this is interchangeable and can be different in each community, depending on the culture and the value system built [45]. In principle, there is a biological difference between men and women, it is really not a problem and therefore it is not necessary to be disputed.…”
Section: Discussionmentioning
confidence: 99%
“…While men are considered strong, rational, mighty and so on. Stereotype like this is interchangeable and can be different in each community, depending on the culture and the value system built [45]. In principle, there is a biological difference between men and women, it is really not a problem and therefore it is not necessary to be disputed.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the above opinion, [16], [17], and [18], stated that the main purpose of initial reading is (1) understanding graphic symbols, (2) sentences, (3) having the ability to spell, and (4) re-expressing writings. Furthermore, [19], [20] reported that there are five levels in learning to read, namely (1) readiness, (2) initial reading, (3) speed (4) reading wide, and (5) refinement.…”
Section: Introductionmentioning
confidence: 99%
“…However, [20] stated that the main factor to be considered during the development of initial reading skills is the attention of the teacher in the class. This is because students tend to respond in accordance with the teachers' intentions.…”
Section: Introductionmentioning
confidence: 99%